HOW ARE ENGLISH VERB-FORMING SUFFIXES TRANSLATED INTO INDONESIAN? A MORPHOLOGICAL AND CONTRASTIVE LINGUISTIC PERSPECTIVE - Huda, Masrul (Elite : English and Literature Journal, 2025)
This study examines the morphological and semantic equivalence between English verb-forming suffixes {-ize}, {-ify}, {-ate}, and {-en} and their Indonesian equivalents. The data used is sourced from Oxford Advanced Learner's Dictionary (2010), English-Indonesian Dictionary (2008), and Kamus Besar Bahasa Indonesia (2008). The analysis focuses on how the English verb derivation process is translated and matched in Indonesian, which often lacks morphologically equivalent verb-forming suffixes. The study identifies equivalence phenomena in the form of convergent equivalence, divergent equivalence, absence of equivalence, and distributional differences between the two languages. The results show that although there are many lexical equivalents, Indonesian relies more on prefixes and phrase constructions than suffixes to form derivative verbs. This difference reflects the different typological characters between English which is more synthetic and Indonesian which is more analytic and agglutinative in word formation. The findings make an important contribution to the development of cross-language equivalence theory as well as practical applications in the fields of translation and language learning.